Regional Volume Tables for Eucalyptus Hybrid (Based on the Data from Muzaffarnagar) - Singh, Jai; Singh, Omkar; Negi, M. S.; Banwal, N. R. (Indian Forester, 1995)
In this article the data for preparation ofthese tables was obtained from Muzaffarnagar road side plantations. Single tree data of 85 trees was collected. Different models were tried. The equation having the best fit for volume calculations has been used.